2002
DOI: 10.1002/pds.748
|View full text |Cite
|
Sign up to set email alerts
|

The nature and frequency of potential warfarin drug interactions that increase the risk of bleeding in patients with atrial fibrillation

Abstract: AF patients discharged on warfarin were frequently prescribed concomitant medications that increase bleeding risks. These patients should be closely monitored and counseled to watch for signs of bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
32
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 51 publications
4
32
0
2
Order By: Relevance
“…However, the type of most frequently prescribed concurrent medicines varies between studies and countries, probably because of different therapeutic traditions and selection of medicines [18,19,29]. The use of potentially interacting medicines among anticoagulant users varies substantially between studies (up to 80% is seen in prescription database studies and around 50% in clinical case control studies) [10,18,19,29].…”
Section: Discussionmentioning
confidence: 99%
“…However, the type of most frequently prescribed concurrent medicines varies between studies and countries, probably because of different therapeutic traditions and selection of medicines [18,19,29]. The use of potentially interacting medicines among anticoagulant users varies substantially between studies (up to 80% is seen in prescription database studies and around 50% in clinical case control studies) [10,18,19,29].…”
Section: Discussionmentioning
confidence: 99%
“…In many countries, warfarin is the coumarin of first choice. Potential drug interactions during anticoagulant therapy with warfarin have been shown to be a frequent issue, as well [8,9]. Among 134,833 patients receiving long-term warfarin therapy, 109,998 (81.6%) were prescribed a concurrent prescription for at least one PID [8].…”
Section: Discussionmentioning
confidence: 99%
“…These drugs were grouped as antibiotics, nonsteroidal antiinflammatory drugs, and other medications, including amiodarone, omeprazole, sertraline, phenytoin, heparin, and cisapride. 6 …”
Section: Study Variablesmentioning
confidence: 99%
“…[3][4][5] In a previous study, we found that Ϸ20% of AF patients receive combined warfarin-antiplatelet therapy. 6 The goals of the current study in elderly AF patients are to examine the influence of patient-specific factors on concomitant warfarin-antiplatelet therapy and the potential impact of combined therapy on major bleeding risk.…”
mentioning
confidence: 99%